Epigenetic regulation of SST2 expression in small intestinal neuroendocrine tumors - Klomp, Maria J.; Refardt, Julie; van Koetsveld, Peter M.; Campana, Claudia; Dalm, Simone U.; Dogan, Fadime; van Velthuysen, Marie-Louise F.; Feelders, Richard A.; de Herder, Wouter W.; Hofland, Johannes; Hofland, Leo J. (Frontiers in Endocrinology, 2023)
Background Somatostatin receptor type 2 (SST2) expression is critical for the diagnosis and treatment of neuroendocrine tumors and is associated with improved patient survival. Recent data suggest that epigenetic changes such as DNA methylation and histone modifications play an important role in regulating SST2 expression and tumorigenesis of NETs. However, there are limited data on the association between epigenetic marks and SST2 expression in small intestinal neuroendocrine tumors (SI-NETs). Methods Tissue samples from 16 patients diagnosed with SI-NETs and undergoing surgical resection of the primary tumor at Erasmus MC Rotterdam were analysed for SST2 expression levels and epigenetic marks surrounding the SST2 promoter region, i.e. DNA methylation and histone modifications H3K27me3 and H3K9ac. As a control, 13 normal SI-tissue samples were included. Results The SI-NET samples had high SST2 protein and mRNA expression levels; a median (IQR) of 80% (70-95) SST2-positive cells and 8.2 times elevated SST2 mRNA expression level compared to normal SI-tissue (p=0.0042). In comparison to normal SI-tissue, DNA methylation levels and H3K27me3 levels were significantly lower at five out of the eight targeted CpG positions and at two out of the three examined locations within the SST2 gene promoter region of the SI-NET samples, respectively. No differences in the level of activating histone mark H3K9ac were observed between matched samples. While no correlation was found between histone modification marks and SST2 expression, SST2 mRNA expression levels correlated negatively with DNA methylation within the SST2 promoter region in both normal SI-tissue and SI-NETs (p=0.006 and p=0.04, respectively). Conclusion SI-NETs have lower SST2 promoter methylation levels and lower H3K27me3 methylation levels compared to normal SI-tissue. Moreover, in contrast to the absence of a correlation with SST2 protein expression levels, significant negative correlations were found between SST2 mRNA expression level and the mean level of DNA methylation within the SST2 promoter region in both normal SI-tissue and SI-NET tissue. These results indicate that DNA methylation might be involved in regulating SST2 expression. However, the role of histone modifications in SI-NETs remains elusive.